Analysing Factors Leading to Catastrophic Expenditure in Surgical Health Care - Kuzu, Serdar; Kablan, Ali; Demir, Ibrahim (ESKISEHIR OSMANGAZI UNIV, 2025)
Catastrophic health expenditure (CHE) occurs when households reduce their basic expenses to finance health services in a certain period and when individuals' out-of-pocket expenses exceed or cover a large portion of the household's expenditure or income. This study analyzes the relationship between the CHE level and the share of public health expenditures in overall health expenditures (HE), an essential indicator of the health system's structure and the country's income level. The study found that the proportion of public HEs in total HEs and per capita income calculated using purchasing power parity had a statistically significant negative impact on the risk of CHEs for surgical procedures.
Keywords: Health Economics; Catastrophic Health Expenditure; Surgical Health Service; Gross domestic product; SURGERY; Business & Economics